(Dis)orientation and Design Preferences Within an Unfamiliar Care Environment: A Content Analysis of Older Adults' Qualitative Reports After Route Learning. Issue 1 (January 2022) - O'Malley, Mary; Innes, Anthea; Wiener, Jan M.
Ensuring that environments are designed to cater for those with decreasing orientation, perceptual and mobility skills, is an example of how environments are being changed to become more age and dementia friendly. However, environmental design should directly involve potential users of the environment to ensure that their views are accounted for. Four open-ended questions, focusing on orientation strategies, reasons for disorientation, and design preferences, were given to 32 older adults after they had completed a route learning task through an unfamiliar environment. A Content Analysis found a strong focus on participants' ability to memorize routes based on verbally encoding the route and on their ability to remember landmarks, with the reports linking closely to cognitive theories of navigation. Design suggestions included the importance of a homely and welcoming environment, memorable features, and access to the outdoors. The findings can be used inform age and dementia friendly design principles.